Front Cover: Photoactive Molecular‐Based Devices, Machines and Materials: Recent Advances (Eur. J. Inorg. Chem. 42/2018). Issue 42 (2nd November 2018) - Baroncini, Massimo; Canton, Martina; Casimiro, Lorenzo; Corra, Stefano; Groppi, Jessica; La Rosa, Marcello; Silvi, Serena; Credi, Alberto
Abstract : The Front Cover shows, in a pop art style, a multiphotochromic tetra(azobenzene)methane derivative in its various configurational isomers, which can be reversibly interconverted by light in solution and, peculiarly, in the solid state. This is an example of how photoactive molecules can be arranged into supramolecular structures to yield light‐responsive molecular devices, machines, and materials. More information can be found in theMicroreview by A. Credi et al. For more on the story behind the cover research, see theCover Profile .